وجه آخر لفكر ابن رشد: مواقف دينية وسياسية - فؤاد أحمد (International Institute of Islamic Thought, 2013)
اشتهر ابن رشد بدعوته إلى الارتقاء بالقول الفلسفي عن حيثيات التاريخي وملابسات الجزئي جاعلا من البرهان خطابه، ومن الإنسان بما هو إنسان مخاطبه. ومهمتنا في هذه الدراسة هي أن نذهب في اتجاه آخر، لإثبات وجه آخر لفلسفة ابن رشد يكشف عن بعض مواقفه الدينية والسياسية والاجتماعية؛ من قبيل مقارنة الأديان واستعادته لبعض الأحداث المؤسسة في تاريخ الحضارة الإسلامية، وفي تاريخ الدولة المغربية والحكم بالأندلس، وتدوينه لبعض التمثلات الاجتماعية السائدة في زمنه بخصوص العلاقات بين العرب والبربر. الغرض من البحث هو تتبع هذه التفاصيل التاريخية لفلسفة ابن رشد باعتبارها مدخلا لفهم طريقة تمثله وقراءته لبعض القضايا الدينية والأحداث التاريخية والظواهر الثقافية وطريقة استعادته لها في نصوصه. It is commonly known that Ibn Rushd separates the philosophical discourse from the circumstances of history and surroundings of the details, considering demonstration (Burhān) as an inherent property of his discourse, and Man to whom this discourse is addressed. The purpose of this study is to highlight some of Ibn Rushd's religious, political, and social positions. Examples of these are his study of comparative religion, reproduction of some of the foundational events in the history of Islamic Civilization, specifically history of Moroccan dynasties, and writing of social representations concerning the relationships between the Arabs and the Berbers. The article will review historical features of Ibn Rushd's philosophy, to understand his interpretations and reproduction of some religious issues, historical events, and cultural phenomena.